PENGARUH KOMPETENSI GURU DAN MOTIVASI BELAJAR SISWA TERHADAP PRESTASI BELAJAR SISWA SMP NEGERI 4 PADANGSIDIMPUAN - Kholid Umar (Universitas Muhammadiyah Tapanuli Selatan, 2019)
This study aims to measure the impact of teachers competence at SMP N 4 Padangsidimpuan on student achievement. The survey conducted using 250 student respondents. It knows that one of the purposes of teaching and learning process is an increased understanding of the students who will eventually reflect in their achievements. A critical factor for improving student achievement is teachers competence. Teachers who lack skill in the field could undermine the result of that goal. The data will collect a questionnaire containing 25 questions. Data of this study meets the classical assumption means can be used to analyse the influence of independent variables using simple regression analysis. The result is showing that the organisation of secondary education need to continue to develop teachers’ competence. With competencies that are always updated and adjusted to the development needs of current knowledge, teachers have better equipped to assist their students in achieving a proud achievement. Keywords: Teachers’ Competence, Student Achievement, SMP